Implementation of Buying Selling for Children Who Have Not Grown Up - Wahidah Z, Wahidah Z (Abdurrauf Journal of Islamic Studies, 2024)
In this overall context, the practice of shopping and delivering favors to neighbors is a good way to shape children's character and teach them values that are important in daily life, while ensuring that buying and selling transactions are carried out in compliance with the religious and ethical principles held by the individuals who carry them out. However, in Tanah Bara village, parents often teach their young children to shop at stalls or small shops to buy some necessities such as sugar, soap, coffee, and other items. When children buy and sell without being accompanied by parents or adults, such as their parents owning a shop, of course, their children make transactions with other people without being supervised by their parents, without knowing what the contract is. The child only sees how his parents sell and does the same thing. Purchases made by minors that occur anywhere. Usually, children buy kitchen utensils and cellphones from their friends, without being accompanied by their parents. For example, Salmiati, one of the children who met in the research area, admitted to buying her parents' cigarettes and also bought her own cellphone. Likewise, Ryan bought coffee, sugar, and cigarettes when told by his parents to immediately rush to buy them, and once also bought a cellphone, if he bought a cellphone with two people he was not free to choose what cellphone he wanted. Dalam keseluruhan konteks ini, praktik berbelanja dan mengantarkan bantuan kepada tetangga merupakan cara yang baik untuk membentuk karakter anak-anak dan mengajarkan mereka nilai-nilai yang penting dalam kehidupan sehari-hari, sekaligus memastikan bahwa transaksi jual beli dilakukan dengan mematuhi prinsip-prinsip agama dan etika yang dipegang teguh oleh individu yang menjalankannya.Namun di kampung Tanah Bara seringkali orang tua mengajarkan anak-anak mereka yang masih kecil untuk berbelanja di warung atau toko kecil untuk membeli beberapa kebutuhan seperti gula, sabun, kopi dan barang-barang lainnya. Pada saat anak melakukan jual beli itu tanpa didampingi orang tua atau orang dewasa, seperti orangtuanya punya warung pastinya anaknya melalukan transaksi dengan orang lain tanpa diawasi oleh orang tuanya, tanpa mengetahui bagaimana akadnya. Anak tersebut hanya melihat bagaimana cara orang tuanya berjualan dan melakukannya dengan yang sama juga. Pembelian yang dilakukan oleh anak dibawah umur yang terjadi dimana saja. Biasanya para anak membeli alat-alat dapur dan handphone dari kawan sendiri, tanpa didampingi orang tua. Contohnya, yang dilakun Salmiati salah seorang anak yang ditemui dikawasan peneliti mengakui membeli rokok orang tuanya dan juga pernah memeli handphone sendiri. Begitu juga yang dilakukan royan membeli kopi, gula, rokok ketika disuruh orang tuanya langsung bergegas untuk membelikannya, dan pernah juga membelikan handphone, jika dia membeli handphone dengan orang dua dia tidak bebas memilih handphone apa yang dia inginkan